2014
DOI: 10.4238/2014.october.31.8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression analysis of PpSUT2 encoding a sucrose transporter in pear

Abstract: ABSTRACT.A 1794-bp cDNA fragment was amplified from mRNA isolated from pear (Pyrus pyrifolia NaKai. Cuiguan) leaves by using primers based on the sequences generated during the analysis of the pear transcriptome. The 597-amino acid sequence encoded by the cDNA was compared with the sequences in GenBank, and it was found to be similar to that of members of the sucrose-proton cotransporter family. The hydrophobic protein, which was predicted to have 11 transmembrane domains, was designated as PpSUT2. Realtime fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…SUT proteins, known as sucrose/H + cotransport proteins, are plant-specific and highly hydrophobic proteins with 12 transmembrane structural domains [ 61 ]. In this study, we found that most SUTs had 12 transmembrane structural domains, which was similar to the previous report [ 62 ]. In the present study, we also observed that the CASUT2 and SmSUT2 had 10 and 11 transmembrane structural domains, respectively, which were different from other SUT proteins.…”
Section: Discussionsupporting
confidence: 91%
“…SUT proteins, known as sucrose/H + cotransport proteins, are plant-specific and highly hydrophobic proteins with 12 transmembrane structural domains [ 61 ]. In this study, we found that most SUTs had 12 transmembrane structural domains, which was similar to the previous report [ 62 ]. In the present study, we also observed that the CASUT2 and SmSUT2 had 10 and 11 transmembrane structural domains, respectively, which were different from other SUT proteins.…”
Section: Discussionsupporting
confidence: 91%